Comparative phenotypic resolution of spontaneous, D2-like and D1-like agonist-induced orofacial movement topographies in congenic mutants with dopamine D2 vs. D3 receptor "knockout" - Tomiyama, Katsunori (2004)
Using a novel system, the role of D2-like dopamine receptors in distinct topographies of orofacial movement was assessed in mutant mice with congenic D2 vs. D3 receptor knockout, and compared with findings in D1A mutants. Under spontaneous conditions, D2 mutants evidenced increased vertical jaw movements and unaltered horizontal jaw movements, with reductions in tongue protrusions and incisor chattering; in D3 mutants, only incisor chattering was reduced. Given previous evidence that D1A mutants show reduced horizontal but not vertical jaw movements, this indicates that apparent oppositional D1-like:D2-like interactions in the regulation of composited jaw movements may in fact reflect the independent actions of D2 receptors to inhibit vertical jaw movements and of D1A receptors to facilitate horizontal jaw movements. Effects of the D2-like agonist RU 24213 to exert greater reduction in horizontal than in vertical jaw movements were not altered prominently in either D2 or D3 mutants. The D1-like agonists A 68930 and SK&F 83959 induced vertical jaw movements, tongue protrusions, and incisor chattering; induction of tongue protrusions by A 68930 was reduced in D2 mutants. D2 receptors exert topographically specific regulation of orofacial movements in a manner distinct from their D1A counterparts, while D3 receptors exert only minor regulation of such movements.